(untitled) (Journal of the College of Basic Education, 2024)
The current research seeks to identify virtual autism and its relationship to excessive use of electronic games among children. In order to achieve the objectives of the current research, the researcher adopted the descriptive, correlational approach through a sample of autistic children in autism centers in Baghdad, where the research sample reached (250) male and female children, and in order to collect the necessary data and information, the two research tools (virtual autism, use excessive use of electronic games) and verifying the appropriate psychometric properties for them in terms of validity and reliability. After applying the two research tools, the research reached the following results: There is a high level of hypothetical autism among children at the Autism Center in Baghdad There are no statistically significant differences between male and female autistic children in the level of hypothetical autism There is a high level of excessive use of electronic games among children in autism centers in Baghdad There are no statistically significant differences between male and female autistic children in the level of use of electronic games. There is a statistically significant relationship between virtual autism and excessive use of electronic games among children in autism centers.